Radiometric parameters of the sacrum and pelvis, affecting the spine and pelvic balance in the frontal plane, in healthy volunteers - Staude, Volodymyr; Radzishevska, Yevgenya; Zlatnyk, Ruslan (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2017)
Objective: to study in healthy volunteers radiometric parameters of sacrum and pelvis, affecting the spinal-pelvic balance in the frontal plane and their relationship to each other. Methods: we examined 36 healthy student volunteers (25 males and 11 females aged 17 to 23 years). The average height was 173 cm (from 168 to 183), average body mass index — 22.23 (from 17.90 to 29.38). Standing X-ray examination performed in all the volunteers. X-rays were measured: 1) the angle of the cranial sacral bone plate by the method of R. E. Irvin in frontal plane; 2) the angle of the pelvic tilt; 3) the angle of rotation around the sacrum axis by method of A. Orel; 4) width of sacroiliac joint in the ventral, dorsal and medial portions. Results were assessed using statistical methods. <span style="font-size: 14.0pt; mso-bidi-font-size: 9.0pt; font-family: ’Times New Roman’; mso-fareast-font-family: ’Times New Roman’; color: #221e1f; mso-ansi-language: RU; mso-fareast-language: RU; mso-bidi-language: AR-SA;">Results:<span style="font-size: 14.0pt; mso-bidi-font-size: 9.0pt; font-family: ’Times New Roman’; mso-fareast-font-family: ’Times New Roman’; color: #221e1f; mso-ansi-language: RU; mso-fareast-language: RU; mso-bidi-language: AR-SA; mso-bidi-font-style: italic;"> the majority of volunteers (81 %) had asymmetric joint space width of sacroiliac joint, which accompanied pelvic and sacral tilt and sacral bone rotation. The sacral slope measured in 95 % of patients, pelvis — 83 %, sacral rotation in 92 %. The width of the joint space of volunteers was (3.3 ± 0.9) mm. Using cluster analysis all volunteers were divided into four clusters (groups), characterized by certain parameters. In the first group examined joint space width was symmetrical in all portions, pelvic tilt and sacral slope were the same, the rotation of sacrum decreased. Joint asymmetry found in two groups of volunteers in the third and fourth groups (39 %, 14 persons) and three parts — other (42 %, 15 people). Found that 20 volunteers (56 %) had joint space asymmetry, pelvic tilt and sacral slope, sacral rotatio 3°, the maximum deviation (more than 3°) these indicators are recorded in 7 volunteers (19 %).